Understanding Breast Implant Illness, Before and After Explantation: A Patient-Reported Outcomes Study. (July 2020) - Wee, Corinne E.; Younis, Joseph; Isbester, Kelsey; Smith, Arvin; Wangler, Brooke; Sarode, Anuja L.; Patil, Nirav; Grunzweig, Katherine; Boas, Samuel; Harvey, Donald J.; Kumar, Anand R.; Feng, Lu-Jean
Abstract : Background: Breast implant illness (BII) after aesthetic breast augmentation remains a poorly defined syndrome encompassing a wide spectrum of symptoms. While previously published series have observed overall symptomatic improvement after breast implant removal, 1–3 there is a lack of studies evaluating changes in specific symptoms over time. The purpose of this study was to gain an understanding of symptoms associated with BII, and to evaluate how these symptoms change after removal of breast implants and total capsulectomy (explantation). We hypothesized that patients presenting with BII would experience both immediate and sustained improvement in constitutional symptoms after explantation. Methods: A retrospective study of all patients who underwent explantation by a single surgeon over 2 years was conducted. Repeated-measures analysis of variance accounting for dependency was used to compare symptoms before and after surgery. Multivariate analyses and linear regression models were used to examine the impact of patient- and implant-related factors on changes in symptoms. Results: Seven hundred fifty patients met inclusion criteria. Mean preoperative survey score (26.19 ± 11.24) was significantly different from mean postoperative survey score at less than 30 days (9.49 ± 7.56) and greater than 30 days (9.46 ± 7.82, P < 0.001). Patients with a BMI greater than 30 or those with clinically detectable contracture on examination showed greater improvement on their survey scores ( P = 0.039, 0.034, respectively). Conclusions: Although BII encompasses a large range of symptoms, subjects in this study demonstrated significant and sustained improvement in 11 common symptom domains. This improvement was demonstrable within the first 30 days postoperatively and was maintained beyond 30 days. The study demonstrated a strong association of explantation and specific symptom improvement within the patient population studied. Future investigation will further elucidate possible biologic phenomena to better characterize the pathophysiology and mechanism of BII.